A Graphene Oxide–Based Sensing Platform for the Determination of Methicillin-Resistant Staphylococcus aureus Based on Strand-Displacement Polymerization Recycling and Synchronous Fluorescent Signal Amplification. (September 2016) - Ning, Yi; Gao, Qiang; Zhang, Xiaoqing; Wei, Ke; Chen, Lingli
To develop new technology for detecting methicillin-resistant Staphylococcus aureus (MRSA), a novel fluorescent biosensor based on Klenow fragment (KF)–assisted target recycling amplification and synchronous fluorescence analysis was created. Carboxy-fluorescein (FAM)–labeled single-stranded DNA (ssDNA) containing a capture probe and a signal probe was adsorbed onto the surface of graphene oxide (GO) via π-stacking interactions, resulting in the fluorescence quenching of the dye. When target and primer were introduced, the fluorescence was restored due to P0 being completely released from the surface of the GO. Meanwhile, by using the KF and exploiting the synergistic effect of FAM and the double-stranded DNA (dsDNA)–SYBR Green I duplex structure, the fluorescence in this detection system was considerably amplified and the sensitivity was improved. The proposed strategy for mecA gene analysis showed a good linear range from 1 to 40 nmol/L, with a lower limit of detection of 0.5 nmol/L. In addition, a bacterial sample harboring the mecA gene was also detected, and its lower detection limit was up to 300 colony-forming units (CFU)/mL. Accordingly, this biosensor exhibits high sensitivity and selectivity and has great potential for early clinical diagnosis and treatment.